2001
DOI: 10.1038/sj.cr.7290075
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of IGF-1R signaling sensitizes urinary bladder cancer cells to mitomycin-mediated cytotoxicity

Abstract: A major problem which is poorly understood in the management of bladder cancer is low sensitivity to chemotherapy and high recurrence after transurethral resection. Insulin-like growth factor 1 receptor (IGF-1R) signaling plays a very important role in progression, invasion and metastasis of bladder cancer cells. In this study, we investigated whether IGF-1R was involved in the growth stimulating activity and drug resistance of bladder cancer cells. The results showed: The mRNAs of IGF-1, IGF-2 and IGF-1R were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 27 publications
2
29
0
1
Order By: Relevance
“…In patients with human epidermal growth factor receptor 2-negative breast cancer, the decreased expression of IGF1R was correlated with an improved response to chemotherapy (59). Blocking IGF1R signaling facilitates treating bladder cancer cells that are insensitive to chemotherapy (60). Similar phenomena have been reported for prostate and ovarian cancer when IGF1R signaling is blocked (61,62).…”
Section: Igf1r and Chemotherapy Resistancesupporting
confidence: 51%
“…In patients with human epidermal growth factor receptor 2-negative breast cancer, the decreased expression of IGF1R was correlated with an improved response to chemotherapy (59). Blocking IGF1R signaling facilitates treating bladder cancer cells that are insensitive to chemotherapy (60). Similar phenomena have been reported for prostate and ovarian cancer when IGF1R signaling is blocked (61,62).…”
Section: Igf1r and Chemotherapy Resistancesupporting
confidence: 51%
“…IGF1R targeting has been linked with enhancement of chemosensitivity in several tumour cell types. In bladder cancer, IGF1R antisense oligonucletide transfection was shown to enhance sensitivity to mitomycin-C. 55 Scotlandi et al 56,57 demonstrated dramatic (410-fold) sensitization to doxorubicin in Ewing's sarcoma cells using IGF1R antisense, dominant negative receptor or monoclonal antibody. 58 It is possible that the greater magnitude of chemosensitization in this tumor may relate to the fact that, unlike prostate cancer, Ewing's sarcoma is inherently chemosensitive.…”
Section: Igf1r Gene Silencing Enhances Sensitivity To Dna-damaging Agmentioning
confidence: 99%
“…These factors have been implicated in chronic inflammatory diseases, 55 prostate, 56 and bladder cancer. 57 Overexpression of IGF-I and underexpression of IGFBP 3 and 5 may lead to hyperplasia of the bladder smooth muscle. 58 Interestingly, IGF is decreased in the urine of IC patients 59 and an anti-proliferative factor purified from urothelial cells of IC patients has been shown to stimulate the production of IGF binding protein 3.…”
Section: Insulin-like Growth Factorsmentioning
confidence: 99%